Comparative study of the dynamics of Mimas-Tethys system at different resonances - Jha, Sarita; Jha, Goind Kumar (International Journal of Advanced Astronomy, 2017)
Here we have done the comparative study on the dynamics of Mimas-Tethys system at Â and Â resonances along with secular resonance of all inner satellites and Saturnâ€™s oblateness. We have drawn Poincare surface of sections and Time-series graph to compare their effect.